Dynamic behaviour of FPSO in Kikeh field under different loading conditions - Nishanth, R. (Asian Research Publishing Network, 2016)
The depletion in natural gas and oil in shallow waters due to extensive extraction along with the increase in its demand has led engineers to develop the floating production platforms which can thrive well in the adverse conditions of deep waters. Floating production Storage and Offloading (FPSO) system has proven to be one of the most promising platforms in the development of offshore oil and gas resources that would be otherwise impossible or uneconomical to tap. In this study, an uncoupled dynamic analysis is performed using the Sesam HydroD software to study the response of FPSO under the action of unidirectional random waves in Malaysian waters in operating conditions in the Kikeh Field. The results can be referred for conceptual design of the FPSO system in Malaysian waters. Â© 2006-2016 Asian Research Publishing Network (ARPN).